Inhibition of gastric acid secretion with omeprazole affects fish specific dynamic action and growth rate: Implications for the development of phenotypic stomach loss - Moffatt, Kelsy; Rossi, Mark; Park, Edward; Svendsen, Jon Christian; Wilson, Jonathan M. (Frontiers in Physiology, 2022)
An acid-secreting stomach provides many selective advantages to fish and other vertebrates; however, phenotypic stomach loss has occurred independently multiple times and is linked to loss of expression of both the gastric proton pump and the protease pepsinogen. Reasons underpinning stomach loss remain uncertain. Understanding the importance of gastric acid-secretion on the metabolic costs of digestion and growth will provide information about the metabolic expense of acid-production and performance. In this study, omeprazole, a well characterized gastric proton pump inhibitor, was used to simulate the agastric phenotype by significantly inhibiting gastric acidification in Nile tilapia. The effects on post-prandial metabolic rate and growth were assessed using intermittent flow respirometry and growth trials, respectively. Omeprazole reduced the duration (34.4%) and magnitude (34.5%) of the specific dynamic action and specific growth rate (21.3%) suggesting a decrease in digestion and assimilation of the meal. Gastric pH was measured in control and omeprazole treated fish to confirm that gastric acid secretion is being inhibited for up to 12 hours post-treatment (p<0.05). Gastric evacuation measurements confirm an increased evacuation time from the stomach in omeprazole treated fish. These findings reinforce the importance of stomach acidification in digestion and growth and present a novel way of determining true costs of gastric digestion.